Efeitos da clonidina nas respostas cardiovasculares ao pinçamento aórtico infra-renal. Estudo experimental no cão - Achôa, Renato Viccário (2003)
BACKGROUND AND OBJECTIVES: Infrarenal aortic cross-clamping is associated to cardiovascular effects. Clonidine, an α2-agonist, determines bradycardia and hypotension. This study aimed at analyzing the effects of clonidine on the cardiovascular function of dogs submitted to infrarenal aortic cross-clamping. METHODS: This randomized study involved 16 mixed breed dogs randomly distributed in two groups: G Control - no clonidine; and G Clon - clonidine (5 μg.kg-1 immediately before aortic cross-clamping, followed by 2 μg.min-1.m2 until the end of the study. All dogs were submitted to infrarenal aortic cross-clamping during 45 minutes. Hemodynamic parameters were measured at control (C), 10 (Ao10) and 25 (Ao25) minutes after aortic cross-clamping, and 10 (DAo10) and 25 (DAo25) minutes after aortic unclamping. RESULTS: There were significant differences between groups in heart rate, mean blood pressure and cardiac index (G control > G Clon) during aortic cross-clamping. Afteraortic unclamping there were significant differences between groups in heart rate (G Control > G Clon), and right atrium and pulmonary capillary wedge pressures (G Clon > G Control). During aortic cross-clamping both groups have shown significant increase in right atrium pressure, pulmonary capillary wedge pressure, stroke volume index and left ventricular systolic work index, and significant decrease in pulmonary vascular resistance index. There has been significant increase in mean blood pressure, pulmonary artery pressure, cardiac index and right ventricular systolic work index in the G Control. The clonidine group has shown significant heart rate decrease. After aortic unclamping, both groups have shown significant heart rate and mean blood pressure decrease, while right atrium pressure and stroke volume index remained high. Right ventricular systolic work index remained high in the control group, while cardiac index values returned to close to baseline values. In the clonidine group, right atrium pressure, pulmonary wedge pressure and systolic index remained significantly high. CONCLUSIONS: In dogs under our experimental conditions, continuous intravenous clonidine has attenuated cardiovascular responses to infrarenal aortic cross-clamping.